2016
DOI: 10.1016/j.freeradbiomed.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of equine vitamin E deficient neuroaxonal dystrophy identifies upregulation of liver X receptor target genes

Abstract: Specific spontaneous heritable neurodegenerative diseases have been associated with lower serum and cerebrospinal fluid α-tocopherol (α-TOH) concentrations. Equine neuroaxonal dystrophy (eNAD) has similar histologic lesions to human ataxia with vitamin E deficiency caused by mutations in the α-TOH transfer protein gene (TTPA). Mutations in TTPA are not present with eNAD and the molecular basis remains unknown. Given the neuropathologic phenotypic similarity of the conditions, we assessed the molecular basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 59 publications
(89 reference statements)
4
45
0
Order By: Relevance
“…2b). The gene CYP7A1 is another example where a novel first exon has been annotated and extended in our version of the transcriptome [13] (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). The gene CYP7A1 is another example where a novel first exon has been annotated and extended in our version of the transcriptome [13] (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Further improvements to this transcriptome would include providing tissue-specific UTR lengths and allowing for a more clear depiction of differences in gene structure between tissues. The improved UTR structure provided by our transcriptome has already shown its utility in the horse community by defining isoform and gene boundaries of MUTYH and TOE1 [23] as well as providing an alternative start exon for CYP7A1 [13]. …”
Section: Discussionmentioning
confidence: 99%
“…In gene array studies with vitamin E supplementation and depletion, regulatory effects were observed with many genes, but unexpectedly genes encoding for proteins with an antioxidant activity were not much more affected than others . However, regulatory effects were observed with NRF2, PPARγ, and LXR that can be redox regulated and are known to be involved in the antioxidant response . In response to increased levels of free radicals and oxLDL, the up‐regulation of CD36 expression at the transcriptional level via PPARγ, NRF2, and LXR may contribute to the antioxidant response by restoring cellular levels of vitamin E .…”
Section: Modulation Of Signaling Pathways By Vitamin E That Prevent Tmentioning
confidence: 99%
“…However, all eight vitamin E analogues can influence signaling albeit often they influence the activity of these enzymes with different strength. (D) These enzymes can modulate the activity of transcription factors such as PXR, PPARα/γ, and LXRα/β, with regulatory effects on vitamin E metabolic enzymes (CYP3A, CYP4F2) and transport proteins (αTTP, ABCA1/G1, and CD36) involved in determining the cellular levels of vitamin E. requirement to elevate the cellular levels of vitamin E to limit the damaging effects of free radicals, for example, by increasing the transport, enrichment or limit the metabolism of vitamin E (13,55,56,61). Moreover, only a limited number of antioxidant genes were modestly up-regulated by vitamin E deficiency (13)(14)(15)(16)(17).…”
Section: Modulation Of Signaling Pathways By Vitamin E Relevant For Imentioning
confidence: 99%
“…RNA-seq analysis was performed on snap-frozen gluteal muscle obtained by percutaneous needle biopsy from six healthy Arabian horses, as part of a previous study (64). Frozen muscle was ground to powder using a Biopulverizer (BioSpec Products, Inc.), and total RNA was extracted using TRIzol/chloroform, as previously described (158). To eliminate genomic DNA contamination, DNase treatment was performed on column (Direct-zol RNA MiniPrep Plus Kit, Zymo Research Corp.) using TURBO DNase (Thermo Fisher Scientific, Inc.).…”
Section: Construction Of a Rna Transcriptome Library From Horse Musclementioning
confidence: 99%